HATE SPEECH ON SOCIAL NETWORKS AND TRADITIONAL MEDIA IN REPUBLIC OF N. MACEDONIA - Majhosev, Andon; Denkova, Jadranka; Osmanov, Shenaj (Journal of process management and new technologies, 2020)
The media, especially social networks as a means of mass communication, have an extremely important role in promoting diversity, their respect, tolerance and equality, non-discrimination. Despite this, they often become promoters of hate speech. More recently, in addition to traditional media, hate speech has found a new way to manifest itself - through social media, the Internet, whose popularity and widespread use allows certain content to reach the widest audience. The paper addresses hate speech in terms of its presence on social networks and traditional media. The aim is to show the situation in the Republic of Macedonia regarding this issue. Thereby, through the method of descriptive analysis, supported by a series of examples from practice, it is concluded that in the Republic of Macedonia the presence of abuse of media and social networks is noticeable, in order to disrespect diversity, spread prejudice, intolerance and stereotypes.